2016
DOI: 10.1002/jbm.a.35827
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation of periodontal pathogens on hydroxyapatite surfaces: Implications for periodontium damage

Abstract: Biofilm formation of periodontal pathogens on teeth surfaces promotes the progression of periodontal disease. Hence, understanding the mechanisms of bacterial attachment to the dental surfaces may inform strategies for the maintenance of oral health. Although hydroxyapatite (HA) is a major calcium phosphate component of teeth, effect of biofilm formation on HA surfaces remains poorly characterized. In this study, biofilm-forming abilities by the periodontal pathogens Aggregatibacter actinomycetemcomitans Y4 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…produced strong biofilms by which they gradually increased after 2 to 7 days of incubation (Adetunji and Isola 2011;Mueller et al 2007). A study by Jaffar et al (2016) demonstrated that Actinomycetemcomitans and Porphyromonas gingivalis produced biofilm from days two to seven, with differing attachment ability. The present study demonstrates that strong biofilms formed on day three.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…produced strong biofilms by which they gradually increased after 2 to 7 days of incubation (Adetunji and Isola 2011;Mueller et al 2007). A study by Jaffar et al (2016) demonstrated that Actinomycetemcomitans and Porphyromonas gingivalis produced biofilm from days two to seven, with differing attachment ability. The present study demonstrates that strong biofilms formed on day three.…”
Section: Resultsmentioning
confidence: 99%
“…To detach the biofilms, 100 μl of 95% ethanol was added into each well. The solubilized biofilm formations were finally measured by the micro plate reader (Tecan Infinite 200 PRO, Austria Gmbh) at the wavelength of 570 nm (Jaffar et al 2016). The experiments were performed in triplicate.…”
Section: Biofilm Assaymentioning
confidence: 99%
“…The study design is illustrated in Fig. S5 and biofilm formation was induced using a previously reported method 65 . The single-species biofilm model, instead of a multi-species biofilm, was used as a simplified model to evaluate various testing conditions as described below.…”
Section: Methodsmentioning
confidence: 99%
“…The microplate is re-solubilized by 150μl of 95% ethanol. Then, plate was measured at 570 nm by a microtiter plate reader (7) . According the optical density of the samples were classified Mean OD value (> 0.240) as strong biofilm,(0.120 -0.240) as moderate biofilm and (< 0.120) as weak biofilm (8) .…”
Section: Biofilm Susceptibility Assaymentioning
confidence: 99%
“…After forming biofilms on 96-well plates previously described (7) . The minimum biofilm inhibitory concentration (MBIC) were measured.…”
Section: Determination Of Minimum Biofilm Inhibitory Concentration (Mmentioning
confidence: 99%